Difficult decisions in times of constraint: Criteria based Resource Allocation in the Vancouver Coastal Health Authority - Dionne Francois; Mitton Craig; Damji Rizwan; Campbell Duncan; Bryan Stirling (BMC, 2011)
Abstract Objectives The aim of the project was to develop a plan to address a forecasted deficit of approximately $4.65 million for fiscal year 2010/11 in the Vancouver Communities division of the Vancouver Coastal Health Authority. For disinvestment opportunities identified beyond the forecasted deficit, a commitment was made to consider options for resource re-allocation within the Vancouver Communities division. Methods A standard approach to program budgeting and marginal analysis (PBMA) was taken with a priority setting working committee and a broader advisory panel. An experienced, non-vested internal project manager worked closely with the two-member external research team throughout the process. Face to face evaluation interviews were held with 10 decision makers immediately following the process. Results The recommendations of the working committee included the implementation of 44 disinvestment initiatives with an annualized value of CAD $4.9 million, as well as consideration of possible investments if the realized savings match expectations. Overall, decision makers viewed the process favorably and the primary aim of addressing the deficit gap was met. Discussion A key challenge was the tight timeline which likely lead to less evidence informed decision making then one would hope for. Despite this, decision makers felt that better decisions were made then had the process not been in place. In the end, this project adds value in finding that PBMA can be used to cover a deficit and minimize opportunity cost through systematic application of criteria whilst ensuring process fairness through focusing on communication, transparency and decision maker engagement.